(untitled) (European Journal of Marketing and Economics, 2023)
China Pakistan Economic Corridor (CPEC) initiates different energy projects, infrastructure ventures and business economic zones within Pakistan. The extensive Chinese investment, worth 62 billion, have long-term impacts on the economy as well as financial institutions of Pakistan. The banking economy are probable to generate an innovative stream of revenues, in the future outlook under CPEC projects. This study is significant in gauging the financial institutions performance and value creation, under CPEC policy. It will enables the institutions in realizing their future planning strategies and achieving their corporate goals. This study contributes in estimating the performance of financial institutions through shareholder value creation, under the CPEC policy in Pakistan. The analyses of this study was furnished by incorporating panel data techniques. The time span of the study is taken since the inception of CPEC agreement i.e. 2012 to 2016. The identification of financial institution`s value creation dynamics, is also one of the major contribution of this study. The paper analysis demonstrates that leverage, dividend policy, and return on equity has statistically significant effect on financial institution`s shareholder value. Moreover, the study results reveals that CPEC does have significant effects on the Pakistan`s financial institutions value creation.